TELADAN TOKOH ALKITAB BAGI MODEL PENDIDIKAN KEPEMIMPINAN KRISTEN - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
Christian leadership has not run as it should be called as a true Christian leader according to the Bible, this happens not only in Christian family life but also in churches and Christian religious organizations, even in society and government whose positions and responsibilities are played by people who claim to be Christian. Several facts are presented in this study as evidence. While the practice that has been carried out for a long time by the Bible characters appointed in this study shows good leadership practices and can be imitated by current and future Christian leaders because these figures also experience leadership challenges that are not small and even threaten their lives and integrity and faith in God. The research method was carried out by library research. The results of this study show examples of Bible characters whose leadership is good and pleasing to God, in other words a Christian leadership model that is finishing well and can be used as a reference guide in Christian leadership education.